Comparison between land suitability and actual crop distribution in an irrigation district of the Ebro valley (Spain) - Martinez Casasnovas, J.A.=700 1 Klaaáe, A.; Nogues, J.; Ramos, M.C.
(En, Es)
Ilus., 35 ref.
Keywords: VOCACION DE LA TIERRA; EVALUACION; TIERRAS; ROTACION DE CULTIVOS; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH